The narrow corner - Maugham, W. Somerset (London : Vintage Books, 2001)
On his way home from a remote Pacific island, Dr Saunders travels with two strangers: the treacherous Captain Nichols, and Fred, a handsome Australian with a shadowy past. Driven to shelter from a storm on the island of Kanda, the trio meet good-natured Erik Christessen and his fiancee, the cool and beautiful Louise.
Keywords: Ship captains -- Fiction; Gamblers -- Fiction; Malay Archipelago -- Fiction